The Court of Justice of the European Union: Do all roads lead to Luxembourg? - Rosas, Allan (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2025)
Since its establishment in the early 1950s, the European Court of Justice, seated in Luxembourg, has played a key role in managing and developing the European integration architecture. Yet, with subsequent developments, the Luxembourg Court appears to have gained even more importance, particularly in the constitutionalization of the European integration process. Today, this has reached such an extent that one can ask whether all roads lead to Luxembourg rather than to the political EU institutions in Brussels and beyond, or to the capitals of the EU Member States. The present paper, based on an annual lecture in honour of Professor and Foreign Minister Krzysztof Skubiszewski, seeks to provide examples of areas where the case law of the Court has been particularly consequential and to explain why the Court has become more influential. However, the paper concludes by arguing that the role of the Court should not be overstated and that, in any case, its enhanced role is explained by many constitutional and legislative developments beyond the control of the Court itself. Moreover, the reader will be reminded that the Union’s judicial system is not limited to the two Union Courts (the Court of Justice and the General Court) but that its backbone is formed by the national courts of the Member States.